Otimização da composição de corantes naturais usando planejamento de misturas - Teixeira, Valéria Maria Costa (2021)
Artificial dyes are a category of additives with no nutritional value, introduced in foods and beverages with the sole purpose of giving them color, making them more attractive. The substitution of artificial colors by natural ones is a trend in the market because, in addition to acting as a dye, these natural substances also have bioactive properties. The present study aimed to determine the composition of mixtures of natural dyes composed of nanoencapsulated curcumin (yellow color), hibiscus extract (red color), and spirulina extract (blue-green color) with less color difference (ΔE *) compared to artificial colors (yolk yellow, apricot yellow, tartrazine, and strawberry red). The color data (a *, b *, and L *) obtained from a ternary mixture design applied to natural dyes, were compared to the data obtained for the artificial dyes, through the color difference (ΔE *). All artificial colors and mixtures were applied in two simulated mediums (citrate buffer pH 3 and phosphate buffer pH 6.9), as well as in natural yogurt (pH 4.0). For each medium and each artificial dye, a mathematical model was obtained to describe the color difference between the natural dye and artificial dye mixture. All mathematical models were able to describe the experimental data, except for the model for the strawberry red dye applied in citrate buffer. In general, the factors that most influenced the models significantly were the pure encapsulated curcumin and hibiscus extract, in addition to the binary interaction of these two components that led to an approximation of the mixture to the color determined for artificial dyes. The highest values of the determination coefficient were obtained for the models of all dyes applied in yogurt (R2 and R2 adjusted> 99.9). The results obtained with the color parameters (L *, a *, b *, C * and h °) of all samples evaluated in the mixture planning and artificial colors in all mediums (citrate and phosphate buffers, and yogurt) were submitted to Principal Component Analysis (PCA), resulting in the formation of 3 groups of samples. The optimization carried out to minimize the color difference was not successful in the experimental validation, mainly due to the alteration of the raw material for obtaining the hibiscus extract, with different sources used in the preparation of the experimental models and in the validation. However, it still has coloring capacity and greater health benefit to consumers when used in substitution to artificial colors.